Application SIMPUS (Sistem Informasi Manajamen Puskesmas) with TAM Theory (Technology Acceptance Model) at Puskesmas Setabelan in Surakarta - Noor, Frieda Ani; Prastyoningsih, Aris; Pratiwi, Ajeng Maharani; Rahayu, Retnaning Tyas; Deniati, Ema Novita (PT Inovasi Pratama Internasional, 2024)
Based on the results of the preliminary study, Puskesmas Setabelan in implementing the SIMPUS application has not been maximized because at the end of each month the internet network is often erroneous because it does not have a good provider, there are still new employees who have not received socialization related to the use of the SIMPUS application, and the patient's online registration has not been opened due to the condition of the community who are still unfamiliar with technology. So the researcher is interested in analyzing how effective the acceptance of the use of the SIMPUS (Puskesmas Management Information System) application is using the TAM (Technology Acceptance Model) theory at the Setabelan Health Center in Surakarta City. This type of research is qualitative and descriptive with data collection methods in-depth interviews with 11 informants including SIMPUS coordinators, SIMPUS programmers, nurses, midwives, pharmacists, dental nurses and administrative staff. The sample selection method used purposive sampling method.